Anthropocentric sayings in Mexican Spanish and Uzbek: a Sociocultural Approach - Velázquez, Virna; Bakhronova, Dilrabo (CIENCIA ergo-sum; Vol. 32 (2025): CIENCIA ergo-sumDO - 10.30878/ces.v32n0a12, 2024)
To understand sociocultural and coding phenomena in both cultures, this study examines Mexican and Uzbek proverbs. It assesses their cultural significance and communicative intent, considering the complexity of associated opinions. The analysis highlights how these proverbs reflect ingrained popular values and knowledge from childhood, emphasizing their role in constructing meanings in everyday discourse. The research underscores their importance for cultural transmission and demonstrates the complexity of their interpretation, influenced by the value system and the individual subject’s experience.